How Has ‘operational Resource Calculator’ Modelling Contributed to Biosecurity Operational Preparedness in New Zealand: A Case Study of the Use of a Foot-and-mouth Disease Operational Resource Calculator Between 2011 and 2014 - Nagle, Deirdre (Auckland University of Technology, 2015)
This dissertation is a case study reviewing how the use of Foot-and-Mouth Disease (FMD) Operational Resource Calculator model has contributed to developing biosecurity preparedness in New Zealand. The case study of the Biosecurity Response Services contract from 2011-2014 explores the preparedness themes from this period which are compared against the key themes from three New Zealand Emergency Events that occurred in the past five years. These themes are analysed and the role the Operational Resource Calculator in building biosecurity preparedness is explored. The findings from this case study identified that the use of the FMD Operational Resource Calculator has supported and guided the growth of the National Biosecurity Capability Network, helping to identify specific gaps in capability and target recruitment. The calculator has also enabled the capability within the National Biosecurity Capability Network for response operations to be tested and to measure capability in peacetime. This has proved important for political support of the network, trailing a potentially risky new model for operational biosecurity preparedness. In addition, the Operational Resource Calculator, can be an iterative tool, therefore achieving longevity which can be utilised to measure capability against future FMD models developed for biosecurity response preparedness.
Keywords: FMD; Resource modelling